Sensory Acceptability of Low Salt Buffalo Calf Meat Rolls Enriched with Dried Plum Powder (DPP) and Dried Apple Pomace Powder (DAPP) during Refrigerated Storage - Kumar Singh, Pradeep; Kumar, Surender; Yadav, Sanjay; Bishnoi, Suman; Rani, Reetu; Pathera, Ashok (Journal of Meat Science, 2026)
The study was planned with an objective to evaluate the sensory features during refrigerated storage of a functional product i.e, low salt buffalo calf meat rolls enriched with dietary fiber by incorporating dried plum powder (DPP) and dried apple pomace powder (DAPP). The scores for colour and appearance declined with advancement in storage period irrespective of the treatments and on 15th day of storage, the colour and appearance scores for all the treatments were between 6.0 to 7.0 indicating moderate to very good acceptability. Similarly flavour scores decreased significantly(P≤0.05) in all the treatments with the advancement of storage days however flavour scores of all the treatments were comparable with control at the end of 15 days and except the treatment T3, the scores for all other treatments were above 6.0. There was significant decline noticed in texture, juiciness and tenderness scores in all treatments with increase in storage days and at the end of storage of 15 days, all treatments except T3 had comparable tenderness scores. Over all acceptability(OAA) scores decreased significantly (P≤0.05) in all the treatments with advancement in storage period and except T3, no significant difference in OAA was noticed among different treatments and scores were well above 6.0.